Temporal and spatial variation of the phytoplankton community in the Chahnime Reservoirs-Sistan - َAhmad Gharaei; Javad Miradr Harijani; Abdolali Rahdari; Mehdi Keikha; Hashem Khandan Barani; Roghaye Karami (بوم‌شناسی آبزیان, 2016)
This study investigated seasonal changes in density and diversity of phytoplankton, chlorophyll a content, and some environmental characteristics in the Sistan region during 2014. Totally, we detected 28 genera that belonged to five groups of Chlorophyta (12 genera), Bacilloriophyta (7 genera), Cyanophyta (5 genera), Dinophyta (3 genera), and Euglenophyta (1 genus). We observed that Chlorophyta contributed to the maximum density and diversity followed by Bacilloriophyta, Cyanophyta and Dinophyta. The mean Shannon index varied from 1.7 to 2.3 during the study period. Maximum (3.6×104 cells 1p1) and minimum (1.1×104 cells 1p3) densities were recorded. The present study revealed that Phytoplankton groups have different relationships to environmental factors of pH, temperature and nutrients that have a greater role in the changes of phytoplankton in the reservoirs. In this study the annual average chlorophyll a was 2.36 µg/l, which reservoirs of Chahnime grouped into oligotrophic regions. These types of studies are prerequisites for evolving fish culture programs and management of water resources.